Е-Learning as a Future-oriented Aspect of Foreign Language Communicative Competence Develop - Zaitseva, N. V. (My University, 2017)
Importance of the information and communication technology in every specialist activity is undisputed today. To train a successful graduate who is going to be in great demand as an employee, a university should teach students not how to learn, but how to develop own competences. It is not enough to be a high-educated specialist; in order to get a job and to obtain a promotion one should demonstrate readiness to work and communicate globally. Foreign language communicative competence is one of the most valuable employee’s advantages over competitors/
Keywords: communication technology; students; foreign language